2012
DOI: 10.3354/meps09802
|View full text |Cite
|
Sign up to set email alerts
|

Absence of countergradient and cogradient variation in an oceanic silverside, the California grunion Leuresthes tenuis 

Abstract: Spatial adaptations that maximize a species' fitness in its local environment, particularly in the form of countergradient variation (CnGV = genotypic influences counteract environmental effects on trait variation) and cogradient variation (CoGV = genotypic influences accentuate environmental plasticity), have been documented in many estuarine and anadromous fishes. However, their prevalence in more oceanic fishes, where extensive gene flow and reduced environmental selection may preclude local adaptation, rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Our laboratory trial, however, did not find evidence of sex-dependent growth rates; hence, size differences between sexes in the wild likely result from different birth dates. In addition, the size difference between males and females does not increase after year 1 (Brown et al, 2012).…”
Section: Sourcementioning
confidence: 84%
See 4 more Smart Citations
“…Our laboratory trial, however, did not find evidence of sex-dependent growth rates; hence, size differences between sexes in the wild likely result from different birth dates. In addition, the size difference between males and females does not increase after year 1 (Brown et al, 2012).…”
Section: Sourcementioning
confidence: 84%
“…Sex determination in L. tenuis likely occurs around 20-25 mm, based on experiments in M. menidia and other studies, which indicated that sex is determined just prior to differentiation (Conover and Fleisher, 1986;Conover and Kynard, 1981). This means that fish spawned in March or April would reach the critical sex determination period in May-June (based on growth rate of 0.34 mm/day at 17°C; Brown et al, 2012), at which point photoperiod would be lengthening. For instance in Malibu, CA (34°N), photoperiod would be increasing from 13.5 light hours: 10.5 dark hours to 14.5 light hours: 9.5 dark hours.…”
Section: Sourcementioning
confidence: 93%
See 3 more Smart Citations